A methodology for the validation of temperature profiles from hyperspectral infrared sounders using GPS radio occultation: Experience with AIRS and COSMIC. Issue 3 (13th February 2014) - Feltz, Michelle L.; Knuteson, Robert O.; Revercomb, Henry E.; Tobin, David C.
Abstract This paper presents a methodology for the validation of vertical temperature profile retrievals from infrared and microwave sounders by intercomparison with Global Positioning System (GPS) radio occultation (RO) profiles matched in time and space. GPS RO provides an estimate of atmospheric temperature with a traceable path to absolute standards and well‐characterized structural uncertainty. While the radiosonde network is a longstanding validation reference for sounder temperature profile retrievals, GPS RO has the advantage of homogeneous global coverage that is unbiased toward land or ocean and has the potential of high absolute accuracy in the upper troposphere to middle stratosphere where little water vapor is present. The polar orbiting sounders utilize cross‐track scanning in highly repeatable Sun‐synchronous orbits, while GPS RO is characterized by pseudorandom sampling in time and space. A comparison approach is described which minimizes sampling uncertainties. The impact of including the horizontal averaging inherent in the RO measurements on the statistical validation is shown. In order to demonstrate the method, bias and RMS vertical profiles have been created for global latitude zones for a range of time intervals using NASA Atmospheric Infrared Sounder (AIRS) Level 2 products compared to dry temperature measurements made by the U.S./Taiwan Constellation Observing System for Meteorology, Ionosphere and Climate (COSMIC) network. The bias and RMS error profiles are shown to depend strongly on the vertical averaging applied to the difference profiles but are relatively insensitive to horizontal and temporal mismatch.